Development of A Digital Underhand Pass Test Tool Based on an Android Application - Fatma Setya Handayani; Hartati, Hartati; Azhar, Samsul; Yusfi, Herri; Bayu, Wahyu Indra (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
This research aims to produce a digital lower passing test tool based on an Android application at SMP Negeri 55 Palembang. The type of research used is research and development (R&D), which is research that produces a product in the form of a digital lower passing test tool based on an Android application. The sampling technique in this research was all students in class VII of SMP Negeri 55 Palembang who at that time were studying bottom passing material in learning the game of volleyball. The data collection techniques used are product validity test data, practicality tests and effectiveness tests. The instruments in this research were validation sheets, questionnaires and students' passing tests. The data analysis technique is validity analysis, practicality analysis and effectiveness analysis. Based on the research results, it can be concluded from the research that the bottom passing test tool is said to be very valid, seen from the validator research results, namely an average percentage of 95% with a very valid category. Based on the student response questionnaire, this lower passing test tool is said to be practical to use with a score of 3.83 with a very positive classification. Based on the results of the bottom passing test, using this tool is effective for use in the learning process. The results of the lower passing test were obtained with an average of 16 in the high category. The conclusion of this research is that the Android application-based digital passing test tool is declared to be very valid in its use, this tool is also practical to use, and this tool is effectively used as a support for learning activities in the game of volleyball. The implementation of the results of this research is that the Android application-based digital passing test tool can be used as intended.